(3CKQ GdNOeGJ GdGdcJQhfjI aj JMbjb GdejRI GdJfGaSjI aj bWGY GdeMQhbGJ (B/(3GdCQOfs (3MGdI OQGSjI GdefGUjQ ddRjhJ hGdeMQhbGJs - (3GdYeGQGJ(B, (3RjO eMeO HTjQs ((3YeGf s (3OGQ hGFd ddfTQ h GdJhRjYs, 2021)
(3jgOa gPG GdcJGH Gdi GdJYQa Ydi CKQ GdNOeGJ GdEdcJQhfjI aj JMbjb GdejRI GdJfGaSjI aj bWGY GdeMQhbGJ hHGdJMOjO ddefGUjQ ddRjhJ hGdeMQhbGJ ef NdGd eSJNOej gPg GdNOeGJ(B.(3hGdJYQa Ydi GdeSJhi GdeWdhH dJMbjb GdejRI GdJfGaSjI ddefGUjQ ddRjhJ hGdeMQhbGJ ef NdGd GSJNOGe GdNOeGJ GdEdcJQhfjI Yf WQjb GdYedGA(B. (3cPdc GdJYQa Ydi GdNOeGJ GdEdcJQhfjI GdJj MbbJ CYdi QVG ddYedGA heSJNOejf gPg GdNOeGJ aj TQcI GdefGUjQ ddRjhJ hGdeMQhbGJ(B. (3HGdGVGaI Gdi GdJYQa Ydi GdNOeGJ GdEdcJQhfjI GdJj JDKQ Ydi GdejRI GdJfGaSjI aj bWGY GdeMQhbGJ(B. (3hGdJYQa Ydi CKQ GdYhGed GdOjehZQGajI dYedGA TQcI GdefGUjQ ddRjhJ hGdeMQhbGJ (B((3GdfhY GdGLJeGYj, GdeDgd GdYdej, GdNHQI GdYedjI GdeQcR GdhXjaj, hbWGY GdCYeGd(B) (3aj JaGhJ eSJhi CSJNOGe GdNOeGJ GdEdcJQhfjI aj bWGY GdeMQhbGJ GdefGUjQ ddRjhJ hGdeMQhbGJ(B).s
Keywords: (3GdeMQhbGJ (B- (3GdNOeGJ GdEdcJQhfjI (B- (3GdCQOfs